Uncertainty, flexible labour relations and R&D expenditure - Marco Di Cintio; Emanuele Grassi (Economics and Econometrics Research Institute (EERI), 2013)
This paper examines the effects of uncertainty and flexible labour contracts on the Research and Development (R&D) expenditure. Using a panel of Italian manufacturing firms, we find a hump-shaped relationship between workforce flexibility and R&D outlays. Moreover, as predicted by the real options theory, our results suggest that product market uncertainty reduces R&D efforts and that flexible labour contracts countervail the adverse effect of uncertainty on R&D.
Keywords: D22; D81; J41; O31; 330; Real options theory; R&D; uncertainty; temporary workers